2009
DOI: 10.1093/abbs/gmp090
|View full text |Cite
|
Sign up to set email alerts
|

The properties of NodD were affected by mere variation in length within its hinge region

Abstract: In Rhizobium leguminosarum bv. viciae, NodD, a member of the LysR-type transcriptional regulators, while auto-regulating, activates transcription of other nod genes in the presence of naringenin. A hinge region of NodD was previously identified in our laboratory as a functional region independent of its N-terminal DNA-binding and C-terminal regulatory domain. Further study was carried out to see the possible effect of the length variation in the hinge region on NodD's properties. To our surprise, as many as se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…viciae (Accession NodD: WP_018068348) was investigated. 57 Here, it was observed that the NodD hinge domain does not interact with DNA or ligand molecules but that a wide range of regulatory phenotypes could be generated simply by altering the length of this hinge domain.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…viciae (Accession NodD: WP_018068348) was investigated. 57 Here, it was observed that the NodD hinge domain does not interact with DNA or ligand molecules but that a wide range of regulatory phenotypes could be generated simply by altering the length of this hinge domain.…”
Section: ■ Resultsmentioning
confidence: 99%
“…viciae (85′IAWDPIN-PAESD, 83% hinge domain identity, see Supplementary Figure S1). 57 Second, the newly identified NodD1 hinge domain was used to pinpoint the FdeR hinge domain (84′IAALPAFVPA-EST, 41% identity for the full amino acid sequences, see Supplementary Figure S2). These identified hinge domains are clearly located at the end of the helix-turn-helix DBD, quintessential of the LysR-family of TFs (see Supplementary Figure S1 and S2).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The domain-connecting hinges in many proteins appears to be crucial for preserving their conformation, stability and function [21] , [22] , [23] , [24] , [25] . The domain-connecting flexible regions in the E. coli FKBP22 and the orthologous proteins are largely structured with a lengthy, protease-sensitive helix designated α3 [14] , [15] , [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%